2009
DOI: 10.1292/jvms.001643
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vasoactive Intestinal Polypeptide-Immunoreactive Nerves in the Major Cerebral Arteries of the Quail Anterior Circulation

Abstract: ABSTRACT. Development of cerebral perivascular nerves immunoreactive for vasoactive intestinal polypeptide (VIP) was investigated in the Japanese quails, using immunohistochemistry and quantitative analysis. VIP-immunoreactive (VIP-IR) nerves supplying the anterior circulation appeared on the cerebral carotid artery (CCA) at embryonic day 10 and on the cerebroethmoidal artery (CEA) after hatching. Nerves from the CCA increased greatly in number and spread progressively during successive embryonic stages, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that laminar flow with consistent and relatively high velocity is required to maintain the integrities of the arterial wall, 7 13 where the arterial endothelial cells play an essential role as a mechanoreceptors 14 21 of flow velocity by detecting wall shear stress (WSS). 22 – 26 A certain level of WSS is necessary for stimulating atheroprotective pathways by controlling various chemical mediators. 14 21 , 27 A high oscillatory shear index (OSI) that reflects fluctuations in WSS induces an inflammatory response, including an increase in reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that laminar flow with consistent and relatively high velocity is required to maintain the integrities of the arterial wall, 7 13 where the arterial endothelial cells play an essential role as a mechanoreceptors 14 21 of flow velocity by detecting wall shear stress (WSS). 22 – 26 A certain level of WSS is necessary for stimulating atheroprotective pathways by controlling various chemical mediators. 14 21 , 27 A high oscillatory shear index (OSI) that reflects fluctuations in WSS induces an inflammatory response, including an increase in reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies have shown that laminar flow with consistent and relatively high velocity is required to maintain the integrities of the arterial wall, [7][8][9][10][11][12][13] where the arterial endothelial cells play an essential role as a mechanoreceptors [14][15][16][17][18][19][20][21] of flow velocity by detecting wall shear stress (WSS). [22][23][24][25][26] A certain level of WSS is necessary for stimulating atheroprotective Y. Takehara et al pathways by controlling various chemical mediators.…”
Section: Introductionmentioning
confidence: 99%